The Sociocultural Determinants of Omega-3 Fatty Acids Intake Among Women Experienced 40-days of Postpartum in Indonesia - Rahayu, Yayu Puji; Barkinah, Tut; Khodarsih, Endhang (Jurnal Penelitian Pendidikan IPA, 2023)
Food intake among postpartum women is still a concern due to taboo among cultural people. This study aimed to examine the impact of sociocultural factors on Omega-3 fatty acids intake among women who experienced 40-days postpartum. The data used Indonesia Family Life Survey with total sample 11,135 women. The dependent variables are Omega-3 fatty acids intake which derived from the intake of eggs, fish, meat, and dairy by following the Mediterranean Diet Foundation. The result of this study revealed that only 5% out of total respondents who had adequate Omega-3 fatty acids intake. Based on the multivariate analysis above, the most significant predictors of having adequate Omega-3 fatty acids intake are graduated from undergraduate. Other variables that are significantly related are graduated from junior high school, senior high school, vocational, and others, were Catholic, Protestant, Buddha, Konghucu, from Sunda and other ethnic groups. There is a need for post-natal education to improve eating habits after delivery besides having graduated from university.